Intermediary bank behavior and debt structure under asymmetric information - Kuang, Yida (2024)
This dissertation is aim to built a foundation for the future study. It reviews past literature on the intermediary bank behavior and debt structure under imperfect information market and detailed review a model describing the interaction between intermediary bank and risky firms and adopting credit reallocation and agency problem. Then I present the for a extension version which would be one of the baseline for the future study, and compare technical solutions which the different results due to the change of settings.